Hunger in a food lover's paradise: Understanding food insecurity in Singapore - Glendinning, Emma (Institutional Knowledge at Singapore Management University, 2018)
This report provides a deeper understanding of the food insecurity situation in Singapore. Food insecurity refers to the lack of physical and/or economic access to sufficient, safe and nutritious food. The report sheds light on those experiencing food insecurity and the factors affecting this experience. In addition, it identifies gaps in food support provision and makes recommendations on how these gaps might be filled for a smoother and targeted food support distribution system.